Superior mediastinal paraganglioma initially suspected of being a mediastinal thyroid goiter. Issue 3 (June 2022) - Takahashi, Ryosuke; Kawabe, Hiroaki; Koide, Nobuaki; Tasaki, Akihisa; Ohno, Kazuchika; Ariizumi, Yosuke; Kobayashi, Daisuke; Asakage, Takahiro
Abstract: Paraganglioma is a rare tumor arising from paraganglia. Few reports have described paragangliomas in the superior mediastinum. We report a case of superior mediastinal paraganglioma treated in our department. A 28-year-old woman visited our department because of suspected mediastinal tumor during a medical checkup. Contrast-enhanced CT showed a 39 × 35 × 65-mm tumor with a well-defined border extending from the lower pole of the left thyroid gland to the superior mediastinum. Laboratory tests showed no evidence of catecholamine overproduction. Mediastinal thyroid goiter was the most suspected preoperative diagnosis. We decided to perform a transcervical excision for both diagnosis and treatment. The tumor was easily detached from the lower pole of the left thyroid gland and was not continuous. The tumor capsule was brittle and bled easily. The operating time was 3 h and 11 min, and the amount of bleeding was 571 mL. The pathological diagnosis was paraganglioma. Paragangliomas are characterized by abundant blood flow and are likely to result in a high intraoperative bleeding volume. In addition, if the tumor is functional, circulatory abnormalities can occur during the perioperative period. Accurate preoperative diagnoses are important, and the possibility that paragangliomas can develop in the superior mediastinum should be considered.